Bilateral endogenous endophthalmitis caused by vancomycin-resistant Staphylococcus epidermidis in a neonate - Relhan, Nidhi (J Ophthalmic Inflamm Infect, 2015)
BACKGROUND: Neonatal bilateral endogenous endophthalmitis is rare and often results in devastating visual outcome. FINDINGS: An 18-day-old neonate presented with whitening of the cornea in the left eye. The child was examined under anesthesia, and a diagnosis of bilateral endogenous endophthalmitis was made. Vitreous biopsy from the left eye showed no growth. Blood samples showed growth of Staphylococcus epidermidis which was multidrug resistant (including vancomycin) but sensitive to piperacillin-tazobactam. The patient was managed with bilateral intravitreal injections of piperacillin-tazobactam and systemic cefpodoxime. Systemic and topical antibiotics were given for 3 and 8 weeks, respectively, and infection was controlled. At 2-year follow-up, the right eye is fixing and following to light with clear view of the fundus and the left eye has a clear cornea with red glow of the fundus. CONCLUSIONS: Vancomycin-resistant S. epidermidis may be a cause of endogenous endophthalmitis. Intravitreal piperacillin-tazobactam and systemic cefpodoxime were used to eliminate the infection in this neonate.